2016
DOI: 10.1080/21622965.2015.1109513
|View full text |Cite
|
Sign up to set email alerts
|

Attention and working memory training: A feasibility study in children with neurodevelopmental disorders

Abstract: The current study investigated the efficacy of a game-based process specific intervention for improving attention and working memory in children with Fetal Alcohol Spectrum Disorders (FASD) and Autism Spectrum Disorders (ASD). The Caribbean Quest (CQ) is a 'serious game' that consists of five hierarchically structured tasks, delivered in an adaptive format, targeting different aspects of attention and/or working memory. In addition to game play, the intervention incorporates metacognitive strategies provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 89 publications
0
60
0
Order By: Relevance
“…The researchers concluded that FaceMaze is an effective computer SG to teach children with ASD understand and perform facial expressions, because the results of typical developed and ASD children were similar. The study by Kerns et al (2016) presents Caribbean Quest, a computer SG, which goal is to improve the attention and working memory of children with ASD and fetal alcohol spectrum disorder.…”
Section: Studies Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that FaceMaze is an effective computer SG to teach children with ASD understand and perform facial expressions, because the results of typical developed and ASD children were similar. The study by Kerns et al (2016) presents Caribbean Quest, a computer SG, which goal is to improve the attention and working memory of children with ASD and fetal alcohol spectrum disorder.…”
Section: Studies Resultsmentioning
confidence: 99%
“…The study by Kerns et al (2016) presents Caribbean Quest, a computer SG, which goal is to improve the attention and working memory of children with ASD and fetal alcohol spectrum disorder. The study by Kerns et al (2016) presents Caribbean Quest, a computer SG, which goal is to improve the attention and working memory of children with ASD and fetal alcohol spectrum disorder.…”
Section: Rq1 Which Aspects Of Adaptive Behaviour and Intellectualmentioning
confidence: 99%
“…In recent years, much attention has focused on training the developing brain (see Jolles and Crone 2012 for a review), with the rationale being that training specific cognitive functions (i.e., attention and working memory) during development, can offer advantages in terms of learning capacity. Cognitive training interventions in children with neurodevelopmental disorders have demonstrated gains on trained and/or non-trained tasks (Kerns et al 2017;Robinson et al 2014). It is possible that neuroplasticity, which refers to the life-long process by which the brain adapts to changes in its environment (Pascual-Leone et al 2005), may underlie these cognitive improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Successful engagement of these domains supports the ability to keep information ‘in mind’, attend to appropriate cues and update information as contingencies change. Though many studies have documented deficits in executive function evident in FASD, few studies have attempted to improve these deficits with cognitive domain-specific training despite positive outcomes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%